PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL ( CSR ) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aries Veronica (STIE DWI SAKTI BATURAJA, 2013)
This study aimed to examine the effect of disclosure of social responsibility (Corporate Social Responsibility) to the stock price, which disclosure is measured from the amount of disclosure of each theme is the theme of community, consumer products and theme, the theme of employment, as well as the theme of the environment. Samples were selected by purposive sampling method, as many as 31 manufacturing companies. This study uses multiple regression analysis to test the hypothesis. However, previous test is conducted prior to the data normality using Kolmogorov-Smirnov One Sample Test and classical assumption. The test results together against the hypothesis shows there are influence between social disclosure on stock prices. The test results show that Ha4 partially accepted, which means there is influence between the number of environmental themes disclosure on stock prices while Ha1, Ha2, Ha3 rejected because t arithmetic < t table, which means there is no effect between the number of disclosures social themes, products and consumer and labor to stock prices.